Potential Climate Change Mitigation Opportunities in the Energy Sector in Vietnam - RCEE Energy and Environment JSC (World Bank, Washington, DC, 2017)
The rapid growth of Vietnam's economy, industry, and consumption has resulted in unprecedented growth in energy demand, and its infrastructure for extracting, generating, and distributing energy is expanding to try to meet those needs. Between 2000 and 2005, total primary energy consumption in Vietnam grew 10.6 percent per year. Growth in fossil-fuel consumption was correspondingly high, with coal use growing at 14.9 percent per year, oil use at 8.2 percent per year, and natural gas use at 37 percent per year. From 2002 to 2030, Vietnam's primary energy demand is expected to grow at a rate of 4.4 percent, increasing from 42 megatons oil equivalent (MTOE) in 2002 to 142 MTOE in 2030. This note will focus on Vietnam's potential Greenhouse gas (GHG) emission reductions and possible interventions associated with resource extraction and power generation for grid electricity. Emissions from power generation in industry and transport are covered under the respective sector notes, and reduction of greenhouse gases through management of end-use demand is covered in the context of industry (as the largest energy user) in the industry sector note.